Development of a Gold Nanoparticle Vaccine against Enterohemorrhagic Escherichia coli O157:H7 - Javier I. Sanchez-Villamil; Daniel Tapia; Alfredo G. Torres (mBio, 2019)
ABSTRACT Here we exploit the natural properties of a synthetic nanoparticle (NP) scaffold as a subunit vaccine against enterohemorrhagic Escherichia coli (EHEC). Two EHEC-specific immunogenic antigens, namely, LomW and EscC, either alone or in combination, were covalently linked on the surface of gold nanoparticles (AuNPs) and used to immunize mice prior to challenge with EHEC O157:H7 strain 86-24. LomW is a putative outer membrane protein encoded in bacteriophage BP-933W, while EscC is a structural type III secretion system protein which forms a ring in the outer membrane. The resulting AuNP preparations, AuNP-LomW and AuNP-EscC, showed that the nanoparticles were able to incorporate the antigens, forming stable formulations that retained robust immunogenicity in vivo after subcutaneous immunization. When administered subcutaneously, AuNP-LomW or AuNP-EscC or a combination containing equivalent amounts of both candidates resulted in higher IgG titers in serum and secretory IgA titers in feces. The serum IgG titers correlated with a significant reduction in EHEC intestinal colonization after 3 days postinoculation. In addition, we showed that serum from antigen-coated AuNP-immunized mice resulted in a reduction of adherence to human intestinal epithelial cells for EHEC, as well as for two other E. coli pathotypes (enteropathogenic E. coli [EPEC], encoding EscC, and enteroaggregative E. coli [EAEC], encoding LomW). Further, the serum had antigen-specific bactericidal properties, engaging the classical complement pathway. Overall, our results demonstrate the immunogenicity and stability of a novel nanovaccine against EHEC. These results also strengthen the prospect of development of a synthetic nanoparticle vaccine conjugated to E. coli antigens as a promising platform against other enteric pathogens. IMPORTANCE Enterohemorrhagic E. coli O157:H7 is a human pathogen and the causative agent of diarrhea and hemorrhagic colitis, which can progress to hemolytic uremic syndrome. These complications represent a serious global public health problem that requires laborious public health interventions and safety control measures to combat recurrent outbreaks worldwide. Today, there are no effective interventions for the control of EHEC infections, and, in fact, the use of antibiotics is counterindicated for EHEC disease. Therefore, a viable alternative for the prevention of human infections is the development of vaccines; however, no such vaccines are approved for human use. In this study, we developed a novel gold nanoparticle platform which acts as a scaffold for the delivery of various antigens, representing a nanovaccine technology which can be applied to several disease models.